Photophysical investigation of near infrared emitting lanthanoid complexes incorporating tris(2-naphthoyl)methane as a new antenna ligand - Abad Galán, L.; Wada, S.; Cameron, L.; Sobolev, A.; Hasegawa, Y.; Zysman-Colman, E.; Ogden, Mark; Massi, Massimiliano (ROYAL SOC CHEMISTRY, 2019)
© 2019 The Royal Society of Chemistry. A conjugated β-triketone, tris(2-naphthoyl)methane (tnmH), has been synthesized and successfully utilized as an antenna moiety for sensitization of the trivalent lanthanoids Eu 3+ , Sm 3+ , Yb 3+ and Nd 3+ , in an isomorphous series of mononuclear complexes formulated as [Ln(tnm) 3 (DMSO) 2 ] (Ln 3+ = Nd 3+ , Sm 3+ , Eu 3+ , Gd 3+ and Yb 3+ ). The photophysical properties of the materials were characterized as comprehensively as possible, with overall quantum yields, intrinsic quantum yields based on calculated radiative decays, and sensitization efficiencies reported. This investigation improves understanding of the sensitization processes occurring in the near-infrared (NIR) region, where quantitative data are currently scarce. In fact, the [Yb(tnm) 3 (DMSO) 2 ] and its deuterated analogue, [Yb(tnm) 3 (d 6 -DMSO) 2 ], present high values of overall quantum yield of 4% and 6%, respectively, which makes them useful and readily accessible references for future investigation of NIR-emitting systems.